Rosehip Oil Promotes Excisional Wound Healing by Accelerating the Phenotypic Transition of Macrophages - Lei, Zhiyong; Cao, Zhijian; Yang, Zaiwang; Ao, Mingzhang; Jin, Wenwen; Yu, Longjiang (Planta Medica, 2019)
Poor wound healing is a major and global threat to public health. Efforts have been made to better understand the underlying mechanisms and develop effective remedies, though the advancements that have been made are still limited. As there are no effective and generally applicable therapies available for skin injuries and fibrosis, it is urgent to develop new drugs and therapies that facilitate wound healing and effectively improve scars. In this study, GC-MS analysis was performed to identify the chemical composition of rosehip oil. The excisional wound healing model and the carrageenan-induced paw edema method were respectively applied to evaluate the wound healing activity and anti-inflammatory activity of rosehip oil. Hematoxylin and eosin staining was used to assess the pathological changes of sections, and Sirius-red staining was performed to analyze the ratio of collagen I/III in wound tissues. Immunohistological staining for CD68, CCR7 (CD197), CD163, TGF-β1, and α-SMA was applied to determine the macrophage phenotypes transition (M1-to-M2) and demonstrate the scar-improving efficacy of rosehip oil on wound healing. Results showed that rosehip oil significantly promoted wound healing and effectively improved scars. This efficacy might be exerted by accelerating the macrophage phenotypes transition and inhibiting the process of epithelial-mesenchymal transition.
Keywords: wound healing; excisional wound; anti-inflammatory activity; rosehip oil; Rosa canina; Rosaceae